Preliminary studies in some aspects of amino acids biosynthesis in juveniles of penaeus monocon fabricus - Coloso, Relicardo M.
Some aspects of amino acid biosynthesis in Penaeus monodon Fabricus were studied. Ion-exchange chromatography in conjuction with radioisotope labelling techniques were used to investigate the incorporation of 14C from (U-14C)-acetate into amino acids of precipitable proteins in P. monodon juveniles. Highest 14C radioactivity was found in the acidic amino acids, aspartic acid and glutamic acid. Little but significant radioactivity was observed in alanine, cysteine, glycine, proline, and serine. Amino acids which incorporated little or 14C were arginine, histidine, isoleucine, leucine, lysine, methione, phenylalanine, threonine, tyrosine, and valine. It appears that P. monodon juveniles could not synthesize these amino acids from acetate. The essential nature of these amino acids in P. monodon is discussed.
A method of partially purifying L-glutamate dehydrogenase, a key enzyme in the biosynthesis of non-essential amino acids, from the muscle of P. monodon juveniles is presented. Enzyme extraction with Tris-acetate buffer, ammonium sulfate fractionation, DEAE-Cellulose Chromatography, and Sepharose 4B Chromatography were used. A 260-fold purification was obtained, but the recovery of enzyme activity was low. Possible modifications in the method and the need for further purification are discussed.
P. monodon possesses an enzyme which catalyzes the de novo synthesis of glutamate from alpha-ketoglutarate and ammonia. The enzyme has a pH optimum for the reductive animation of alpha-ketoglutarate between pH 8.0 and 8.2. The low Michaelis-Menten constant (1.03 x 10 negative 4 M) of the enzyme for alpha-ketoglutarate strongly suggests the physiological importance of this pathway in P. monodon. Substrate inhibition by alpha-ketoglutarate at high, non-physiological levels was observed and discussed.
The molecular weight of the native enzyme by molecular sieve chromatography is 320,000 daltons. Subunit studies using SDS-polyacrylamide gel electrophoresis suggest that the enzyme possesses a unique molecular organizaion compared to those derived from other sources.
Theses--(Master in Science in Biochemistry) UPCM
Keywords: Amino Acids